The Portait of Erick Thohir’s Transformational Leadership on Instagram - Hermanto Sihombing, Lambok; Puji Lestari (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Being a competent leader especially is a governmental office is essential. Transformational leadership is one of leadership styles that can be applied when someone becomes a leader. Erick Thohir, Indonesian Minister of State-Owned Enterprises can be included as the leader who applies transformational leadership. Through Instagram, Minister Erick frequently posts his work on Instagram and demonstrates his concern for Indonesian society. Consequently, Instagram has become an essential solution in optimizing a government work system. This study aimed to identify academically and scientifically the use of Instagram in the bureaucratic system to improve service quality based on the various information events obtained by the researchers. The method of this research is using qualitative approach. To analyze the relationship between Instagram and government bureaucracy, the researchers drew upon diverse aspects of the Transformational Leadership theory. The object of this study is @erickthohir's Instagram account as the representative Indonesian governor. The dataset was taken from scientific articles that support this analysis. The results demonstrated that Erick Thohir had implemented Instagram effectively to express his dedication to providing outstanding service to Indonesian society. The existence of Instagram facilitates the government's access to information about the community. As a result, interactions between the government and the community become easier and more efficient.